Difference between revisions of "TrigSimplify Command"

From GeoGebra Manual
Jump to: navigation, search
("typo")
(TrigSimplify don't work for -sin²(x)+1 in GGb)
Line 3: Line 3:
 
;TrigSimplify[ <Expression> ]
 
;TrigSimplify[ <Expression> ]
 
:Simplifies the given trigonometric Expression.
 
:Simplifies the given trigonometric Expression.
:{{example|1=<code>TrigSimplify[1 - sin(x)^2]</code> gives ''cos²(x)''.}}
+
:{{examples|1=<div>
 +
::<code>TrigSimplify[1 - sin(x)^2]</code> gives <u>''-sin²(x)+1''</u>.
 +
::<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1 ]</code> gives ''2 sin²(x)''.</div>}}
 
:{{note|1=<div> See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}
 
:{{note|1=<div> See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}
 
==CAS Syntax==
 
==CAS Syntax==
 
;TrigSimplify[ <Expression> ]
 
;TrigSimplify[ <Expression> ]
 
:Simplifies the given trigonometric Expression.
 
:Simplifies the given trigonometric Expression.
:{{example|1=<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1 ]</code> gives ''2 sin(x)²''.}}
+
:{{examples|1=<div>
 +
::<code>TrigSimplify[1 - sin(x)^2] </code> gives ''cos²(x)''
 +
::<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1 ]</code> gives ''2 sin²(x)''.</div>}}
 
:{{note|1=<div>
 
:{{note|1=<div>
 
:* This command works for the variable ''x'' only! (<code>TrigSimplify[1 - sin(y)^2]</code> gives ''-sin²(y) + 1''.)
 
:* This command works for the variable ''x'' only! (<code>TrigSimplify[1 - sin(y)^2]</code> gives ''-sin²(y) + 1''.)
 
:* See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}
 
:* See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}

Revision as of 08:32, 19 December 2012


TrigSimplify[ <Expression> ]
Simplifies the given trigonometric Expression.
Examples:
TrigSimplify[1 - sin(x)^2] gives -sin²(x)+1.
TrigSimplify[sin(x)^2 - cos(x)^2 + 1 ] gives 2 sin²(x).

CAS Syntax

TrigSimplify[ <Expression> ]
Simplifies the given trigonometric Expression.
Examples:
TrigSimplify[1 - sin(x)^2] gives cos²(x)
TrigSimplify[sin(x)^2 - cos(x)^2 + 1 ] gives 2 sin²(x).
Note:
© 2021 International GeoGebra Institute